Analysis of immunogenic cell death in ascending thoracic aortic aneurysms based on single-cell sequencing data - Tian, Zemin; Zhang, Peng; Li, Xinyang; Jiang, Delong (Frontiers in Immunology, 2023)
Background: At present, research on immunogenic cell death is mainly used for tumor therapy. But in cardiovascular disease, little is known about immunogenic cell death, especially in ascending thoracic aortic aneurysms. Method: Analyzed the ascending thoracic aortic aneurysms single-cell RNA (scRNA) sequencing data to define the cells at play and determine their transcriptomic characteristics. Chi-square test, GO (Gene Ontology) and KEGG (Kyoto Encyclopedia of Genes and Genomes) enrichment analysis, GSEA (Gene Set Enrichment Analysis), Cellchat for cell-to-cell communication analysis were used in this database: Gene Expression Omnibus (GEO). Result: A total of 10 cell types were obtained, namely monocytes, macrophages, CD4T/NK (CD4+T cells and Natural killer T cells), mast cells, B/Plasma_B, fibroblasts, endothelial cells, and cytotoxic T cells, vascular smooth muscle cells, mature dendritic cells. A large number of inflammation-related pathways are present in the GSEA results. A large number of ICD-related pathways were found in the KEGG enrichment analysis of differentially expressed genes in endothelial cells. The number of mature dendritic cells and CTL in ATAA was significantly different from that in the control group. A total of 44 cellular pathways were obtained, of which 9 were associated with immunogenic cell death in endothelial cells. The most important ligand-receptor pair from endothelial cells and fibroblasts to CD4T/NK cells, CTLs and mature dendritic cells is CXCL12-CXCR4. The most important ligand-receptor pair from endothelial cells to monocytes and macrophages is ANXA1-FPR1. The most important ligand-receptor pair from CD4T/NK cells and CTLs to endothelial cells is CCL5-ACKR1. The most important ligand-receptor pair from myeloids (macrophages, monocytes and mDCs) to endothelial cells is CXCL8-ACKR1. Vascular smooth muscle cells and fibroblasts mainly promote inflammatory responses through the MIF signaling pathway. Conclusion: Immunogenic cell death exists in ATAA and plays an important role in the development of ATAA. The target cells of immunogenic cell death may be mainly endothelial cells, which the ACKR1 gene of endothelial cells in aorta can not only promote T cell infiltration through CCL5 ligand, but also promote myeloid cell infiltration through CXCL8 ligand. ACKR1 and CXCL12 may become target genes for ATAA drug therapy in the future.